Attack Level of Brown Planthopper Nilaparvata lugens Stal (Hemiptera: Delphacidae) on Varieties of Rice from Pasaman in Greenhouse - Zulaikha, Eva; Arneti, Arneti; Busniah, Munzir (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2021)
Brown planthopper (BPH) is a major pest on rice plants that can cause hopperburn and crop failure. The study aimed to determine the level of BPH attack on several local rice varieties in the Pasaman Regency. This research was conducted in a greenhouse, Faculty of Agriculture, Universitas Andalas, using a completely randomized design (CRD), with five treatments and five replications. The treatments were four different rice varieties from Pasaman and control (Siganteng, Pulau Batu, Mundam Kuning, Mundam Putih, IR 42). BPH was infested when the rice was five days after sowing. Observation parameters were the percentage and the intensity of the attacks. Observations were done until 15 days after infestation; after the IR 42 variety died 90%. The results showed that the attack rate of BPH on rice varieties from Pasaman was moderate. The lowest percentage of attack occurred in the Mundam Putih variety (94%), while the intensity of the attack was not significantly different from other varieties.